Comparação de projetos arquitetônicos para otimização de eficiência energética e conforto ambiental em aviários de frangos de corte para o oeste do Paraná - Dalmina Júnior, Moacir José (2018)
The high cost of production is one of the greatest challenges in poultry and the energy cost is one of the main factors for the final value of the product. So, the proposed study seeks to minimize and enhance the energetic lighting and ventilation system of broiler houses in the western region of Paraná state, Brazil. The objective of the present study was to develop a comparison of three design models of broiler houses to improve energy efficiency and environmental comfort of confined poultry. Thus the research analyzed two models of broiler houses existing in the market, the open-sided broiler house and the dark house models, in addition to a third model the proposed system that has as characteristics a brise-soleil system and cross ventilation, which uses natural resources to help in the thermal efficiency of the broiler house, minimizing energy costs and providing better animal comfort.Therefore, they result in a production gain, which helps the systems currently used. Thus, the study sought to develop a mixed system between project actions to better use of natural lighting and ventilation, as well as the use of electric heating and ventilation systems that have been used in commercial broiler houses. The models were developed using Autodesk Revit™ software, and the results were obtained through Green Building Studio™. The methodology used was the comparison of the models and analysis of the energy consumption of the buildings during the year. The outcome allowed us to conclude that the broiler house model proposed for this study was 20.97% more efficient than the open-sided model and 58.21% more efficient than the dark house model.